2008
DOI: 10.1631/jzus.b071322
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of the articular cartilage proteoglycan degradation by T-2 toxin and selenium protective effect

Abstract: Abstract:Objective: To identify the relationship between T-2 toxin and Kashin-Beck disease (KBD), the effects of T-2 toxin on aggrecan metabolism in human chondrocytes and cartilage were investigated in vitro. Methods: Chondrocytes were isolated from human articular cartilage and cultured in vitro. Hyaluronic acid (HA), soluble CD44 (sCD44), IL-1β and TNF-α levels in supernatants were measured by enzyme-linked immunosorbent assay (ELISA). CD44 content in chondrocyte membrane was determined by flow cytometry (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…Therefore, the T-2 toxin contamination was proposed as a possible cause of KBD (424). In support of this hypothesis, cell culture studies demonstrated that T-2 toxin can inhibit aggrecan synthesis in human chondrocytes, promote aggrecanases and pro-inflammatory cytokines expression, and aggrecan degradation; selenium can inhibit the effects of T-2 toxin (222). A previous study by the same group showed that selenium can partly block T-2 toxin-induced apoptosis in chondrocytes (82).…”
Section: Clinical Disordersmentioning
confidence: 82%
“…Therefore, the T-2 toxin contamination was proposed as a possible cause of KBD (424). In support of this hypothesis, cell culture studies demonstrated that T-2 toxin can inhibit aggrecan synthesis in human chondrocytes, promote aggrecanases and pro-inflammatory cytokines expression, and aggrecan degradation; selenium can inhibit the effects of T-2 toxin (222). A previous study by the same group showed that selenium can partly block T-2 toxin-induced apoptosis in chondrocytes (82).…”
Section: Clinical Disordersmentioning
confidence: 82%
“…These effects could be reversed by the addition of selenium. The effects of T-2 toxin have also been studied on aggrecan metabolism in human chondrocytes and cartilage in vitro (Li et al 2008). The perturbed balance between aggrecan synthesis and degradation in cartilage might be an important step in the initiation of the cartilage degradation.…”
Section: Kashin-beck Diseasementioning
confidence: 99%
“…Production of TNF-α results in high level of nitric oxide (NO), which in turn induces chondrocyte apoptosis (Clancy et al, 2004). Our previous study showed that T-2 toxin increased the production of TNF-α (Li et al, 2008). Therefore, TNF-α could play an important role in triggering and modulating of T-2 toxin-induced apoptosis.…”
Section: Rt-pcr Detection Of Bax Bcl-xl Bcl-2 P53 Fas and Caspasementioning
confidence: 99%